Analysis of the Document Management Information System Using the Rapid Application Development Method - M. Nurul ihsan; Khairul Umam; Mala Rosa Aprillya; Darmawan (Universitas Muhammadiyah Lamongan, 2026)
The rapid advancement of information technology has pushed higher education institutions to improve document management efficiency, yet many study programs still rely on manual processes or non-integrated storage, causing data duplication, retrieval difficulties, weak security, and inefficient archiving. This study aims to develop a web-based Study Program Document Management Information System using the Rapid Application Development (RAD) method to enable centralized, integrated, and secure document management. The RAD approach comprised four stages: requirements planning, user design, system construction, and testing and implementation. Data were collected through field observations, stakeholder interviews, and analyses of hardware and software requirements. The system was built using PHP and MariaDB as the RDBMS, providing key features such as login authentication with CAPTCHA security, document upload and download, categorization, search, and user management. Based on Black Box Testing, all 35 test cases were executed successfully without failures, yielding a system validity of 100%. Therefore, the developed system is considered valid, feasible, and effective in improving digital document management, administrative efficiency, and accreditation support for study programs. Keywords: Document Management System; Rapid Application Development; Information System; Black Box Testing; Study Program.